Cytochrome P450-mediated inhibition of venlafaxine metabolism by trimipramine. (September 2019) - Kowalewski, Christoph; Haen, Ekkehard; Hiemke, Christoph; Ridders, Florian; Endres, Katharina; Gründer, Gerhard; Paulzen, Michael; Schoretsanitis, Georgios
Abstract : Objective: The aim of this study was to ensure patients' safety and to enhance treatment efficacy, knowledge about pharmacokinetic interactions even in complex clinical situations of polypharmacy is invaluable. This study is to uncover the potential of pharmacokinetic interactions between venlafaxine and trimipramine in a naturalistic sample. Methods: Out of a therapeutic drug monitoring database with plasma concentrations of venlafaxine (VEN) and O-desmethylvenlafaxine (ODV), we considered two groups of patients receiving venlafaxine without known cytochrome P450 confounding medications, taking solely venlafaxine: V0 (n = 905), and a group of patients co-medicated with trimipramine, VTRIM (n = 33). For VEN, ODV and active moiety (sum of VEN + ODV) plasma concentrations and dose-adjusted concentrations as well as ODV/VEN ratios were compared between groups using the Mann–Whitney U test with a significance level of 0.05. Results: Patients co-medicated with trimipramine had higher plasma concentrations of VEN (183.0 vs. 72.0, +154%, P = 0.002) and AM (324.0 vs. 267.5, +21%, P = 0.005) and higher dose adjusted plasma concentrations than patients in the control group ( P = 0.001 and P = 0.003). No differences were found for ODV and C/D ODV ( P < 0.05 for both comparisons). The metabolite to parent ratio, ODV/VEN, was significantly lower in the VTRIM group (1.15 vs. 2.37, P = 0.012). Conclusion: Findings suggest inhibitory effects of trimipramine on venlafaxine pharmacokinetics most likely via an inhibition of CYP 2D6 or by saturated enzyme capacity. The lack of in vitro data hampers the understanding of the exact mechanisms. Clinicians should be aware of drug–drug interactions when combining these agents. Therapeutic drug monitoring helps to ensure treatment efficacy and patients' safety.